2016
DOI: 10.33225/jbse/16.15.693
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Conceptual Change Texts Enriched With Metaconceptual Processes on Pre-Service Science Teachers’ Conceptual Understanding of Heat and Temperature

Abstract: The purpose of this research was to compare the effect of conceptual change texts enriched with metaconceptual processes with the effect of refutational and expository texts on pre-service science teachers’ conceptual understanding of heat and temperature. The durability of the effect of the texts on pre-service science teachers’ conceptual understanding was also examined. A pre-test- post-test experimental research design was employed. One hundred and five pre-service teachers who were enrolled in an Elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…Our results strongly support the suggestions of different authors (Gonz alez Galli et al, 2020;Gresch, 2020;Perez et al, 2022) that enabling students through metacognition and self-regulated learning to regulate their intuitive conceptions may improve students' conceptual knowledge. First empirical studies conducted within this framework already produced preliminary evidence supporting this claim (Perez et al, 2022;Wingert et al, 2022), and studies using different types of metaconceptual interventions also found positive effects on students' conceptual knowledge (Duez, 2020;Kirbulut, 2012;Sabancı et al, 2020;Wiser & Amin, 2001;Yürük et al, 2009Yürük et al, , 2011. Through the experimental design of our study, we could identify the instruction on conditional metaconceptual knowledge as an effective tool to develop conceptual knowledge and enable self-regulation of cognitive biases.…”
Section: Rq1: Intervention Effects On Conceptual Knowledgesupporting
confidence: 51%
See 1 more Smart Citation
“…Our results strongly support the suggestions of different authors (Gonz alez Galli et al, 2020;Gresch, 2020;Perez et al, 2022) that enabling students through metacognition and self-regulated learning to regulate their intuitive conceptions may improve students' conceptual knowledge. First empirical studies conducted within this framework already produced preliminary evidence supporting this claim (Perez et al, 2022;Wingert et al, 2022), and studies using different types of metaconceptual interventions also found positive effects on students' conceptual knowledge (Duez, 2020;Kirbulut, 2012;Sabancı et al, 2020;Wiser & Amin, 2001;Yürük et al, 2009Yürük et al, , 2011. Through the experimental design of our study, we could identify the instruction on conditional metaconceptual knowledge as an effective tool to develop conceptual knowledge and enable self-regulation of cognitive biases.…”
Section: Rq1: Intervention Effects On Conceptual Knowledgesupporting
confidence: 51%
“…However, causal relationships are unknown, and there are only preliminary answers to whether and which metaconceptual teaching strategies can enhance students' conceptual knowledge. Quasi-experimental and qualitative studies provide preliminary evidence that metaconceptual teaching sequences including various activities (e.g., differentiating between scientific and everyday concepts) can enhance students' conceptual knowledge (Kirbulut, 2012;Sabancı et al, 2020;Wiser & Amin, 2001;Yürük, 2007;Yürük et al, 2009Yürük et al, , 2011, but it still needs to be investigated through controlled experiments to what extent specific types of metaconceptual instruction (e.g., instruction on conditional metaconceptual knowledge) affect the development of conceptual knowledge. Additionally, while many authors embed metaconceptual thinking in models of conceptual change, we suggest that embedding it in the framework presented here (i.e., not attempting to change students' conceptions but helping them to self-regulate their conceptions context-dependently) provides a new perspective for instructional strategies based on self-regulated learning and metacognition, and thus novel strategies from educational psychology.…”
Section: Instruction On Conditional Metaconceptual Knowledgementioning
confidence: 99%
“…Many conceptual changes have occurred in the scientific field due to the development of conceptual models. For example, conceptual changing texts (Ozkan & Selcuk, 2016;Yürük & Eroğlu, 2016); cognitive conflict (Labobar et al, 2017;Samsudin et al, 2019), and inquiry learning (Stieff, 2019;Chen et al, 2021); computer simulations (Dega et al, 2013;Fan et al, 2018), and representational (Tytler et al, 2020;Avargil & Saxena, 2023) have all been used as instructional intervention changes to correct students' misconceptions. Nadelson et al (2018) attempt to explain the conceptual change model (CCM) regarding the process of accommodation of conceptual change, which depends on several factors, including students' dissatisfaction with existing ideas (dissatisfaction), understanding of new concepts (clarity), clarity (reasonableness), and usefulness (success).…”
Section: Figure 1 the Theoretical Framework Of Researchmentioning
confidence: 99%
“…Metacognitive skills and motivation are integral components when considering factors that affect the process of conceptual change (Conradty & Bogner, 2016;Taasoobshirazi et al, 2016) after confronting cognitive conflict (Hadjiachilleos et al, 2013;Yürük & Eroğlu, 2016). Promoting students' self-explanations of concepts they encounter daily, arousing their curiosity and interest, and involving them in the learning process can be one way to boost motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Keadaan ini dikenal dengan beberapa istilah. salah satunya adalah konsepsi alternatif (Gómez, 2021;Irmak et al, 2022;Yürük & Eroğlu, 2016).…”
unclassified